Evaluation Of Solitary Polypoid Mass in Colorectal Region with Clinico Pathological Correlation - Saroj, Manish Kumar; Kumar, Tanmay; Bharti, Shreekant; Bhadani, Punam Prasad (Journal of Neonatal Surgery, 2025)
Background: Solitary polypoid masses in the colorectal region are commonly encountered in clinical practice, with potential for both benign and malignant transformation. Accurate diagnosis through clinico-pathological correlation is crucial for proper management. Objectives: The main aim of this study is to evaluate the clinico-pathological correlation of solitary polypoid masses in the colorectal region, focusing on their clinical presentation, colonoscopic findings, and histopathological diagnoses. Materials and Methods: This retrospective study was conducted over a 3-year period (March 2020 To March2023) at AIIMS Patna, including 250 patients diagnosed with solitary polypoid masses through colonoscopy and histopathological examination. Results: The study revealed that the most common clinical symptoms were rectal bleeding and pain, with tubular adenomas being the most frequent histopathological finding (42%), followed by hyperplastic polyps (32%) and inflammatory polyps (14%). A small proportion of cases (4%) showed carcinoma arising from adenomatous polyps. Conclusion: The study underscores the importance of clinico-pathological correlation in the diagnosis of colorectal polyps, emphasizing the need for routine biopsy of solitary polypoid masses to avoid misdiagnoses. Future studies should focus on larger, multi-center prospective research to refine diagnostic and management strategies.